Peripheral Ossifying Fibroma: A Case Report and Review of Literature - C.P. Srinivasan; P. Durgesh (Nigerian Dental Association, 2019)
Peripheral ossifying fibroma (POF) is an infrequently occurring, slowly progressing, innocuous, nodular overgrowth of the gingiva, which belongs to the category of the "reactive lesions of the gingiva." There are several such overgrowths with similar clinical manifestations, but diverse etiology and histopathological features, thus presenting a challenge for the clinician. Thorough clinical examination, radiographic and histopathological features help to establish the diagnosis which is key to the successful management of such lesions. This article describes a case of POF in a 43-year-old male patient. The clinical, radiographic, histologic features, aggressive treatment strategies, relapse and close follow-up of POF are discussed in detail.